Comparisons between XRD of different ball-milled samples of LiNij.xCoxFey02 and LiNii.xCoxAly02 / Nurdalila Mohd Nazeri - Mohd Nazeri, Nurdalila (2012)
LiNio.7Goo.2Feo.1O2 and LiNio.7Coo.2Alo.1O2 with micron sized particle was prepared to obtain nano sized particle by using high energy ball milling (HEBM) method. After the milling process, it causes in reducing the crystallite sizes and more agglomerations to the samples. X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) were used to characterize the samples and all the results were analysed and discussed. The 24 hours of milling has changed the samples from micron size to nano size by using 0.3mm and 0.5mm diameter balls.